Dynamic Routes of Auspicious Khao Lam: Boon Khao Bote Tradition of Buddhist Relatives Group of Phromlok Temple, Phrom Kiri District, Nakhon Si Thammarat Province - Nillakan, Lunjakon; Navakijpaitoon, Nilrat; Lertgrai, Punya; Saengae Saijun, Krittaporn; Thaicharoen, Wichian (International Journal of Psychosocial Rehabilitation, 2020)
The research of Dynamic Routes of Auspicious Khao Lam: Boon Khao Bote Tradition of Buddhist Relatives Group of Phromlok Temple is qualitative research, which emphasizes field study in temple area and communities around Phromlok Temple. Its objective is to study the preparation process of the Boon Khao Bote Tradition of Buddhist Relatives Group of Phromlok Temple and study the dynamic routes of the Boon Khao Bote Tradition of Buddhist Relatives Group of Phromlok Temple. Research results indicate that Boon Khao Bote Tradition of Buddhist Relatives Group of Phromlok Temple consisted of two main Buddhist Relatives Groups, such as ceremonious group and Kho Lam producing group, and the implementation requires 2-3 days. There are dynamics both in the ceremony and Khao Lam production in compliance with social conditions, constituted from learning and systematic development based on faith and tenacity of the group’s power.